Comparative assessment of source-driven toxic metal bioaccumulation and human health risks in edible aquatic organisms from freshwater and estuarine ecosystems - Ruwan Tharanga Perera; Nalin Gunathilaka; Asith Umayanga Dias; Alecsha Sathnara Fernando; Dilshani Sakunthala; Hiruni Gunathilaka; Janitha Liyanage (EQA - International Journal of Environmental Quality, 2026)
Heavy metal contamination in aquatic food sources poses potential risks to human health and ecosystems. This study evaluated the tissue-specific distribution, bioaccumulation patterns, and health risks of selected heavy metals and metalloids (Cr, Mn, Cu, Zn, As, Cd, and Pb) in Etroplus suratensis (freshwater and brackish water) and Scylla serrata (brackish water). Metal concentrations were analyzed in edible and non-edible tissues including muscle, gills, gut, and hepatopancreas. Results revealed significant tissue-specific accumulation influenced by ecological and physiological factors. In Etroplus suratensis, muscle tissues showed elevated chromium levels exceeding permissible limits, while gills, and gut accumulated higher levels of Zn, Mn, and Pb. In Scylla serrata, the hepatopancreas exhibited the highest metal accumulation, whereas body muscle showed extremely high Zn concentrations. Statistical analyses confirmed significant differences among tissues and ecosystems (p < 0.05), and correlation patterns suggested common anthropogenic pollution sources. Multivariate analysis (PCA) indicated that 85.44% of total variance was explained by metal associations linked to environmental inputs. Risk assessment showed no significant non-carcinogenic risk for Etroplus suratensis (HI < 1), while Scylla serrata indicated potential health risks (HI > 1) due to elevated Zn and As. These findings highlight the importance of monitoring heavy metal contamination in aquatic food systems, particularly in estuarine environments.